Analysis of solid phase formation and its impact on slag rheology. (1st September 2017) - Schwitalla, Daniel H.; Bronsch, Arne M.; Klinger, Mathias; Guhl, Stefan; Meyer, Bernd
Highlights: Investigation of crystallization during slag viscosity measurement. Analysis of effect of crystallization on temperature of critical viscosity. A quench furnace is a great asset in analyzing crystal formation in slags. Crystallization has a major impact on slag viscosity. Abstract: High temperature conversion processes are often affected by slag. While other physical attributes of slag also affect the process, the viscosity is regarded as most important in many industrial processes such as steel production or slagging gasification. The mineral matter in these processes often does not have a defined melting point, but stays partially solid within a specific temperature range. It is well known, that solids within a liquid increase the viscosity of the mixture. The effect of the formation of the solid phase during cooldown in a viscosity measurement is analyzed in this study. The effect of atmosphere on crystallization is investigated by analyzing one slag under reducing and oxidizing conditions. Those investigations are performed on the original slag by differential thermal analysis (DTA). Further analyses on quenched samples are performed using X-ray diffraction (XRD) and a scanning electron microscope. The solid fraction of the slag is identified and quantified via XRD. The value of these means to characterize crystallization behavior is discussed, assessed and compared against thermodynamic equilibrium calculations (FactSage®). The DTA is identified as a quick test to get a first impression of the crystallization behavior of a slag. A relationship between the forming of crystals inside a slag and its temperature of critical viscosity is confirmed in this study. Especially gehlenite and akermanite have a major impact on the rheological behavior of the analyzed slags. In the end, the need for crystallization kinetics is identified. This emphasizes that equilibrium calculations should be treated with caution.